Study of purification processes of soil contaminated with uranyl nitrate - Mammadov, Kh.F.; Shiraliyeva, H.N.; Mehtiyev, E.I.; Aliyeva-Jabbarly, U.S.; Guliyev, E.I.; Mirzayev, N.A.; Huseynova, A.H. (Вопросы атомной науки и техники, 2021)
The extraction of uranyl nitrate contaminated soil with weak solutions of nitric and hydrochloric acid, caustic sodium and subsequent washing of soil residues with distilled water leads to a more than tenfold decrease in the content of uranium isotopes (U²³⁸, U²³⁵, U²³⁴, and U²³⁶) in the soil. At the same time, there is a decrease in the content of natural radionuclides (Na²², K⁴⁰, Zn⁶⁵, Sn¹¹³, Sn¹²⁶) in the extracted soil samples. An increase in their content in the extract of the analyzed soil sample corresponds to a decrease in their content in the residue of the extracted soil sample. The combined extraction with weak solutions of these acids and alkalis leads to the enrichment of the soil with nitrates and chlorine-containing compounds of non-radioactive metals. Комбіноване екстрагування забрудненого нітратом уранілу ґрунту слабкими розчинами азотної і соляної кислоти, їдкого натрію і подальше промивання залишків ґрунту дистильованою водою призводять до більше десятиразового зниження вмісту ізотопів урану (U²³⁸, U²³⁵, U²³⁴, and U²³⁶) у ґрунті. При цьому спостерігається зниження також вмісту природних радіонуклідів (Na²², K⁴⁰, Zn⁶⁵, Sn¹¹³, Sn¹²⁶) в екстрагованих зразках ґрунту. Підвищення їх вмісту в екстракті аналізованого зразка ґрунту відповідає зниженню їх вмісту в залишку екстрагованого зразка ґрунту. Комбінована екстракція слабкими розчинами цих кислот і лугів призводить до збагачення ґрунту нітратами і хлорвмісними з'єднаннями нерадіоактивних металів. Комбинированное экстрагирование загрязненной нитратом уранила почвы слабыми растворами азотной и соляной кислоты, едкого натрия и последующее промывание остатков почвы дистиллированной водой приводят к более десятикратному снижению содержания изотопов урана (U²³⁸, U²³⁵, U²³⁴, and U²³⁶) в почве. При этом наблюдается снижение также содержания природных радионуклидов (Na²², K⁴⁰, Zn⁶⁵, Sn¹¹³, Sn¹²⁶) в экстрагированных образцах почвы. Повышение их содержания в экстракте анализируемого образца почвы соответствует снижению их содержания в остатке экстрагированного образца почвы. Комбинированная экстракция слабыми растворами этих кислот и щелочей приводит к обогащению почвы нитратами и хлорсодержащими соединениями нерадиоактивных металлов.